“Giraffe Language" and "Jackal Language": a study of two opposite communication rituals - Longina Strumska (Universiti Kebangsaan Malaysian, 2012)
This paper refers to the “giraffe language” and “jackal language”, which allude to the “non-violent communication” concept according to Marshall B. Rosenberg. The two languages being discussed describe two different types of rhetoric and, at the same time, two opposite communication/social rituals used by people in their everyday life and also in the mass media, and omnipresent in the advertisement. The paper tries to draw attention that contemporary media is based on “jackal language” (often strongly rooted in our culture and mentality) being a language of violence, blocking empathy and stimulating conflicts and tension in interpersonal communication and relationships). Unfortunately media makes a tremendous impact on the customers (especially on young people). This paper aims to propagate and encourage using the “giraffe language” described as the language of love, understanding and clemency. The ‘giraffe language’ encourages constructive, matterof- fact and unbiased communication. A long giraffe’s neck became its symbol - a metaphor of perfect (objectivity) communication.